2022
DOI: 10.1111/mcn.13341
|View full text |Cite
|
Sign up to set email alerts
|

Predicting preschool children's emotional eating: The role of parents' emotional eating, feeding practices and child temperament

Abstract: Emotional eating (EE; defined as overeating irrespective of satiety and in response to emotional states) develops within childhood, persists into adulthood, and is linked with obesity. The origins of EE remain unclear, but parental behaviours (e.g., controlling feeding practices and modelling) and child characteristics (e.g., temperament) are often implicated. To date, the interaction between these influences has not been well investigated. This study explores whether the relationship between parent and child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Interestingly, however, it was not possible to confirm a significant relationship between the pressure to eat and emotional eating, and further research is needed to more thoroughly analyze the mechanism underlying the relationship between these variables. Perhaps there are significant moderators/mediators of this relationship (e.g., intensity of negative affect, child’s body weight; [ 24 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, however, it was not possible to confirm a significant relationship between the pressure to eat and emotional eating, and further research is needed to more thoroughly analyze the mechanism underlying the relationship between these variables. Perhaps there are significant moderators/mediators of this relationship (e.g., intensity of negative affect, child’s body weight; [ 24 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Equally important as physical activity for children with intellectual disabilities is their adequate intake of energy and nutrients, which play a very important role in their development [ 22 ]. Balanced (healthy) eating behavior involves, among other things, starting and ending a meal in response to hunger and satiety signals [ 23 , 24 ]. However, in many studies, (over)eating in the absence of hunger is increasingly being observed in children’s eating patterns, which may be related to the emotional state of the child and the lack or insufficient flexibility in dealing with emotions effectively [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional overeating (EOE) involves excessive food consumption to regulate negative emotions and has been observed from early childhood throughout the lifespan (Messerli-Bürgy et al, 2018;Stone et al, 2022). This eating behavior often incorporates the consumption of energy-dense foods that are high in fat, calories, and sugar, which increases the risk of obesity (Steinsbekk et al, 2016;Messerli-Bürgy et al, 2018;Favieri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This eating behavior often incorporates the consumption of energy-dense foods that are high in fat, calories, and sugar, which increases the risk of obesity (Steinsbekk et al, 2016;Messerli-Bürgy et al, 2018;Favieri et al, 2021). As pediatric obesity is one of the major global health concerns, there has been growing interest in identifying early precursors of obesogenic eating behaviors, including EOE (Haycraft et al, 2011;Topham et al, 2011;Ju et al, 2022a;Stone et al, 2022). Research suggests that EOE is particularly susceptible to the influence of relational and environmental factors beyond genetics (Blissett et al, 2010;Steinsbekk et al, 2016;Ju et al, 2022a;Stone et al, 2022), as well as to child characteristics involving reactivity and regulation (Rothbart and Derryberry, 1981).…”
Section: Introductionmentioning
confidence: 99%